«Տողադարձ» թեմայի ուսուցման մեխանիզմ - Մելքոնյան, Հեղինե (Զանգակ հրատ.)
В данной статье изложен опыт преподавания темы “Перенос” на уроках современного армянского языка: Выделены четыре этапа: 1) изучение правил; 2) оформление особой формулы; 3) перенос данных слов; 4) обнаружение ошибок переноса. Данная методика, по нашему убеждению, может быть эффективно применена не только в вузах, но и в средних учебных заведениях. In the given article we have tried to introduce our experience in teaching “hyphenation” which we have gained during the period of teaching the practical course of Modern Armenian. We offer to teach the topic according to the following four steps: 1. teaching the rules, 2. elaboration of a hyphenation formula, 3. the process of hyphenation, and 4. finding hyphenation mistakes. This is a productive method which can be used not only at higher educational institutions but also at secondary schools.
Keywords: Ուսուցման և դասավանդման մեթոդիկա